Kontribusi Buruh Wanita terhadap Pendapatan Keluarga (Studi Kasus PTPN XII di Kabupaten Malang) - Novita (Jurnal Agribisnis, 2023)
Women's Workers' Contributions to Family Income. The study aimed to find out how much a tea-picking female worker contributes to family income. The population in this study was all female tea-picking workers in Wonosari afdeling numbering 88 people. The sample determination technique used is saturated sampling, where all members of the population are used as samples because the number is relatively small than 100 people. Data retrieval uses observations, interviews, questionnaires, and documentation. Data processing techniques use editing, coding, and tabulating. The data obtained from the results of the study was analyzed using quantitative descriptive methods, presented in table form and analyzed to describe and describe the amount of income contribution provided by tea picking women workers. The results showed the contribution of the income of tea picking women workers to the total family income averaged 41 percent. This shows that female tea picker workers are very helpful to families in meeting the needs in the household.